Mind the gap: Expediting gender parity in MD-PhD admissions - Temperance R. Rowell; Robert A. Redd; Donna S. Neuberg; Loren D. Walensky (JCI Insight, 2020)
The 2018 National MD-PhD Program Outcomes Study highlighted the critical need to increase MD-PhD trainee diversity and close the gender gap in MD-PhD enrollment. This Association of American Medical Colleges imperative prompted us to evaluate trends in female matriculation from our institutional MD-PhD program compared with national data. Based on a 10-year review of Harvard/MIT Medical Scientist Training Program admissions, we observed a sharp and sustained increase in female matriculants for the past 5 years that is well above the national average. We report our experience with achieving gender parity among matriculants of our MD-PhD program, identify the specific stage of the admissions process where the gender balance acutely shifted, and attribute the increase in female matriculation to concrete administrative changes that were put into place just prior to the observed gender balance shift. These changes included increasing the number of faculty participants in application screening and awardee selection and establishing gender balance among faculty decision makers. We believe that adopting basic administrative practices geared toward increasing the diversity of perspectives among admissions faculty has the potential to expedite gender parity of MD-PhD matriculants nationwide and could eventually help achieve gender balance in the national physician-scientist workforce.